Can first trimester vitamin D levels predict adverse maternal outcomes in patients who do not take vitamin D supplements? - Dinçgez, Burcu; Özgen, Gülten; Özgen, Levent (The European Research Journal, 2024)
Objectives: Vitamin D deficiency is claimed to be associated with adverse perinatal outcomes. Here, we aimed to compare adverse maternal outcomes according to vitamin D levels and determine the predictive role of first-trimester vitamin D for adverse maternal outcomes in patients not receiving vitamin D supplementation. Methods: This study was designed as a retrospective study. A total of 232 patients were divided into three groups: vitamin D deficient (n=127), vitamin D insufficient (n=57), and vitamin D sufficient group (n=48). Then, the vitamin D deficiency group was divided into severe (n=72) and mild (n=55) vitamin D deficiency. Sociodemographic characteristics, first-trimester vitamin D levels, and adverse maternal outcomes such as gestational diabetes mellitus, preeclampsia, preterm birth, and intrauterine growth restriction were compared between the groups. The predictive role of first-trimester vitamin D levels for adverse maternal outcomes was evaluated by ROC analysis. Results: Gestational diabetes was more common in the vitamin D deficient group than in the vitamin D insufficient group (P=0.024). However, preeclampsia, preterm delivery, and composite adverse outcomes were more common in the vitamin D deficient group than in the vitamin D sufficient group (P=0.044, P=0.008, and P=0.023, respectively). There was no difference in maternal outcomes between the mild and severe vitamin D deficiency groups. First-trimester vitamin D levels ≤19 ng/mL predicted adverse outcomes with 73.2% sensitivity and 49.2% specificity (AUC=0.630, P=0.006). Conclusions: We recommend screening vitamin D levels in the first trimester, especially in high-risk groups, due to the increased incidence of adverse outcomes. We believe that more research is needed to clarify the relationship between vitamin D and adverse outcomes and the effect of supplementation on these outcomes.